Role of oral flecainide in assessement of atrio-ventricular conduction in symptomatic bifascicular block. (14th October 2021) - Kumar, D; Dwivedi, S.K; Chaudhary, G; Sharma, A; Chandra, S; Vishwakarma, P; Pradhan, A; Sethi, R; Bhandari, M; Shukla, A; Singh, A
Abstract: Background: Intravenous flecainide is used to stress Atrio-ventricular (AV) conduction in patients (pts) with a history of syncope & bifascicular (Bi-Fasc) block. Role of oral flecainide is unclear. Objective: To assess effect of oral Flecainide on infra-Hisian AV conduction in patients with symptomatic Bi-Fasc block. Methods: Pts presenting with syncope & Bi-Fasc block without advanced AVCD on ECG, 24 hr holter or treadmill exercise test were taken. Those with history suggestive of reflex syncope & positive tilt test were excluded. Remaining underwent electro-physiological (EP) study. Pts with HV interval >100ms or intra/infra-Hisian block at rest or incremental pacing were subjected to PPI. Remaining received oral Flacanide 5 mg/kg (max 300 mg) & EP study was repeated after ½ hr, 1 hr, 2 hrs and 3 hrs. Primary end-point was HV ≥100ms or infra/intra-Hisian type IIB or III block. Results: Of 41 pts enrolled for study, 28 patients (mean age 60.0 yrs, mean LVEF 60.7%) were eligible for EP Study. Basal PR interval was 185.8±47.4 ms & mean QRS width was 130.6±18.65 ms. On EP study, 4 (14.3%) with resting HV >100 ms & 6 (21.4%) with HV >100 ms on incremental pacing underwent PPI. Out of remaining 18 pts who were given flecainide, 11 (66.1%) achieved primary endpoint (HV >100 ms in 6, infra-hisian IIB in 2 and 2:1 block in 3 patients). At mean follow up of 6.5 months, 13 (59.1%) out of 22 with PPI had mean 59.1% VP & none of 6 remaining patients had any symptom. Conclusion: Oral Flecainide significantly increases the diagnostic yield of EP study in patients with symptomatic bi-fasc block. Funding Acknowledgement: Type of funding sources: None.